THE EFFECT OF FINANCIAL DISTRESS, LITIGATION RISK, AND GROWTH OPPORTUNITIES ON ACCOUNTING CONSERVATISM WITH LEVERAGE AS MODERING IN MANUFACTURING COMPANIES LISTED IN INDONESIA STOCK EXCHANGE - Yusnaini, Yusnaini (Asosiasi Dosen Akuntansi Indonesia, 2019)
This study aims to examine and analyse the effect of financial distress, litigation risk, and growth opportunities on accounting conservatism with leverage as a moderating variable. The population in this study were 147 manufacturing companies listed on the Indonesia Stock Exchange in the 2015-2017 period, with a purposive sampling technique so that 102 samples were obtained. The data analysis method uses multiple linear regression analysis and interaction testing with the help of the Eviews application program. The results showed that financial distress and litigation risk partially had a positive and significant effect on accounting conservatism, while growth opportunities partially had no effect on accounting conservatism. Simultaneously financial distress, litigation risk, and growth opportunities affect accounting conservatism. Leverage as a moderating variable weakens the relationship of variables, but is not significant in partially moderating the effect of financial distress, litigation risk, and growth opportunities on accounting conservatism in Manufacturing companies listed on the Indonesia Stock Exchange in the period 2015-2017.